Anglicisms Pride and Gay in a Sociopolitical Context: the Phenomenon of ‘Semantic Suicide’ (Linguostylistic Studies, 2022)
This article highlights the issue of new anglicisms pride and gay that has recently entered the Ukrainian language semantic domain and considers the features of their functioning in the social, cultural, and socio-political context. The subject matter of the study is not only the lexical-semantic field of these lexical units in English, their etymology, and the change of semantic interpretation under the influence of sociopolitical factors in the diachrony, but also the nature of lexical-semantic and paradigmatic connections of these lexical units in the Ukrainian language and the specific and adequate equivalents of them in Ukrainian.Lexical-semantic, etymological, and onomasiological analysis of new Anglicisms pride and gay have demonstrated the decisive influence of extralinguistic socio-political factors on the perception of these lexical units in the Ukrainian language. The paradigmatic relations revealed the extralinguistic phenomenon of the so-called ‘seme-suicide’ – the substitution and renaming of concepts. It has been proven once again that random borrowings are a way to hide a specific native denotation (in this case: a pervert) and to plant a foreign phenomenon unacceptable for our culture using de-semanticized lexical signs in the projected paradigmatic relations for a political purpose.The issue of false nominations, in other words, the substitution or renaming of concepts, is due to the differences in sociocultural  and  psycholinguistic  background  of the source  and a target language, including politically-agreed interpretation of English-American realities in Ukraine. Thus, the deconstruction (killing) of language meanings becomes an existential norm and one of the main tools of every totalitarian ideology (in the current conditions – left-liberal).The new anglicisms under consideration are illustrative examples of borrowed anglicisms and manifestations of excessive barbarization of the Ukrainian lexical system, undermining its conceptual and cognitive foundation. The research findings indicate the necessity for a mandatory search for Ukrainian equivalents which may be relevant to foreign language realities or unacceptable for the Ukrainian language system.Priority of a specific lexical unit before a borrowed one is the actualization of the conceptual and cognitive processes of the nation and the national, rather than borrowed creation of reality because the non-borrowed/native lexeme expresses and implies, while the foreign one, particularly in these cases, hides and distorts.
Keywords: Anglicism; new Anglicism; sociopolitical context; barbarization